A Bibliometric Analysis of Publications on University-Industry Collaboration Using VOSviewer and R-biblioshiny - Guofang, Zhan; Rasul, Mohamad Sattar; Omar, Marlissa (Multidisciplinary journal for education, social and technological sciences, 2024)
This bibliometric analysis studied the development trends, publication and citation counts, research themes and trends, and international cooperation models related to university-industry collaboration from 1970 to 2023. Firstly, using a broader set of search terms related to university-industry collaboration, we conducted a comprehensive search of the global literature from 1970 to 2023 in the Web of Science (WoS) database. Secondly, based on inclusion and exclusion criteria, we ultimately selected 592 articles for analysis. Subsequently, we used VOSviewer and R-biblioshiny as analytical tools to extract and analyze relevant data from the selected articles. The study identified the most influential institutions, journals, authors, and countries in this field. Additionally, based on keyword co-occurrence analysis, research related to university-industry collaboration is distributed across five clusters: (1) innovation and technology transfer, (2) internships and work experience, (3) cooperative education and learning outcomes, (4) collaboration models and partnerships, and (5) collaboration barriers, challenges, and sustainability. Recent research has focused on themes such as technology transfer, barriers, benefits, and the motivations driving collaboration.